Morocco's Webinars Ignite Global Academic Resilience in Doctoral Research: Webinar Maroko Memicu Ketahanan Akademik Global dalam Penelitian Doktoral - Nadif , Bendaoud (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: The COVID-19 pandemic triggered significant disruptions in education worldwide, compelling a shift to online learning across various contexts, including in Morocco. Specific Background: In response to this challenge, the Faculty of Letters and Human Sciences at Mohammed V University in Rabat initiated the